Analyzing disparities in transit‐based healthcare accessibility in the Chicago Metropolitan Area - Liu, Dong; Kwan, Mei‐Po; Kan, Zihan (The Canadian geographer, 2022)
Public transit is indispensable for car‐free households to access healthcare. Meanwhile, different households have unequal transit‐based healthcare accessibility due to different socio‐economic factors such as race/ethnicity and car ownership. Few studies have comprehensively explored the inequality in transit‐based healthcare accessibility by integrating both racial/ethnic inequity and car ownership. This study fills the gap with an up‐to‐date analysis of transit‐based healthcare accessibility in the Chicago Metropolitan Area at the census tract level. The results show that the percentage of car‐free households is positively related to transit‐based healthcare accessibility; while a higher percentage of minorities (i.e., Black/Hispanic) is negatively related to transit‐based healthcare accessibility. Among all neighbourhoods with higher percentages of higher‐than‐average car‐free households, Hispanic‐majority neighbourhoods fare the worst; while White‐majority neighbourhoods have much better healthcare accessibility than both Black‐majority and Hispanic‐majority neighbourhoods. Key Messages White‐ and Hispanic‐majority neighbourhoods with higher‐than‐average percentages of car‐free households have the highest and lowest levels of healthcare accessibility respectively. The percentage of car‐free households and minorities are positively and negatively related to the healthcare accessibility score respectively. The racial/ethnic factor has a stronger association with healthcare accessibility outcome than car ownership status. Analyse des disparités en matière d'accessibilité aux soins de santé par les transports en commun dans la région métropolitaine de Chicago Les transports en commun sont indispensables pour permettre aux ménages sans voiture d'accéder aux soins de santé. Cependant, l'accessibilité aux services de santé par les transports en commun est inégale d'un ménage à l'autre en raison de différents facteurs socioéconomiques tels que la race ou l'ethnie et la possession d'une voiture. Peu d'études ont exploré de manière exhaustive l'inégalité d'accès aux soins de santé par le biais du transport en commun en intégrant à la fois l'inégalité raciale ou ethnique et la possession d'une voiture. Cette étude tente de combler cette lacune en présentant une analyse actualisée de l'accessibilité aux services de santé par le transport en commun dans la région métropolitaine de Chicago, à l'échelle des secteurs de recensement. Les résultats montrent que le pourcentage de ménages sans voiture est directement proportionnel à une bonne accessibilité aux soins de santé par le transport en commun, tandis qu'un pourcentage plus élevé de minorités (c'est‐à‐dire Afroaméricains ou Hispaniques) est inversement proportionnel à une forte accessibilité aux soins de santé par le transport en commun. Parmi tous les quartiers où le pourcentage de ménages sans voiture est supérieur à la moyenne, les quartiers à majorité hispanique sont les plus mal pourvus en matière d'accès aux services, tandis que les quartiers à majorité blanche ont un bien meilleur accès à ceux‐ci que les quartiers à majorité afroaméricaine ou hispanique.